2013
DOI: 10.1038/srep03554
|View full text |Cite
|
Sign up to set email alerts
|

Microbial life in the Lake Medee, the largest deep-sea salt-saturated formation

Abstract: Deep-sea hypersaline anoxic lakes (DHALs) of the Eastern Mediterranean represent some of the most hostile environments on our planet. We investigated microbial life in the recently discovered Lake Medee, the largest DHAL found to-date. Medee has two unique features: a complex geobiochemical stratification and an absence of chemolithoautotrophic Epsilonproteobacteria, which usually play the primary role in dark bicarbonate assimilation in DHALs interfaces. Presumably because of these features, Medee is less pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 35 publications
4
98
1
Order By: Relevance
“…Despite findings suggesting that chemolithoautotrophy is the dominant metabolic trait in halocline waters of Mediterranean DHABs (Yakimov et al 2013), the OTUs detected in our study represent prokaryotes that need organic substrates for growth. Available organic carbon that reaches the seafloor of Mediterranean DHABs is expected to be relatively recalcitrant, compared to newer, more labile carbon sources in the overlying water column, but there is no information on available electron donors in DHAB sediments.…”
Section: Methodscontrasting
confidence: 96%
See 1 more Smart Citation
“…Despite findings suggesting that chemolithoautotrophy is the dominant metabolic trait in halocline waters of Mediterranean DHABs (Yakimov et al 2013), the OTUs detected in our study represent prokaryotes that need organic substrates for growth. Available organic carbon that reaches the seafloor of Mediterranean DHABs is expected to be relatively recalcitrant, compared to newer, more labile carbon sources in the overlying water column, but there is no information on available electron donors in DHAB sediments.…”
Section: Methodscontrasting
confidence: 96%
“…While new cell morphologies and ecophysiological traits have been assigned to some of these microorganisms, only recently a more specific picture of the metabolic activities of DHAB microorganisms has started to emerge, e.g. S--oxidizing chemolithotrophy, microaerophilic autotrophy, heterotrophic sulfate reduction, methanogenesis and anaerobic methane oxidation (Borin et al 2009;La Cono et al 2011;Ferrer et al 2012;Pachiadaki et al 2014;Yakimov et al 2013;Alcaide et al 2015). In spite of these recent advances, we still know little about how these microorganisms survive and grow under the prevailing conditions of the DHABs.…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant OTUs belonging to Methanobacteriales or MSBL1 were highly similar (95-99%) to unclassified sequences recovered from other hypersaline meromictic lakes, solar salterns sediments or deep sea-hypersaline anoxic basins, indicating the existence of a yet-undescribed methanogenic group present in extreme hypersaline habitats. Although this assumption is supported by a recent study on Medee brines (Yakimov et al, 2013), in which MSBL1 candidate division was shown to be responsible for the methanogenic fermentation of trimethylamine, further experiments using cultivation and 14 C-assimilation are needed to unambiguously describe the methanogenesis in these high-salt ecosystems.…”
Section: Methanogenesismentioning
confidence: 89%
“…As such, the low-energy yield of nitrification may preclude this process at high salt concentrations, which may partially explain the reduced biomass of AOA and the higher density and phylogenetic diversity of sulfur oxidizers in the BSI layer (Yakimov et al, 2007(Yakimov et al, , 2013. Although the upper salinity limit for autotrophic ammonia oxidation is still uncertain, nitrification appears to be constrained at salt concentrations exceeding 100 g l -1 (Oren, 2011).…”
Section: Bioenergetic Considerationsmentioning
confidence: 99%